503 QUALITY OF LIFE AS A PREDICTOR OF POST-ESOPHAGECTOMY SHORT TERM OUTCOMES AND SURVIVAL. (14th September 2020) - Katz, A; Ramirez-GraciaLuna, J; Kammili, A; Abureida, F; Cools-Lartigue, J; Spicer, J; Mueller, C; Ferri, L
Abstract:  : Most esophageal cancer patients present with symptoms that impact quality of life (QOL). In this study, we sought to determine the influence of QOL at diagnosis on postoperative outcomes and survival (OS). Methods: A prospectively-collected esophagectomy database (2006–17) was queried to identify patients who completed Functional Assessment of Cancer Therapy-Esophageal module (FACT-E). Demographics/tumor/treatment details, operative variables, complications and OS were collected. Statistical analysis was done using Cox regression, logistic regression, ANOVA or Chi-square tests. Results: Of 647 patients underwent esophagectomy in the study period, 359 how completed FACT-E at diagnosis were included in the study (age 64 ± 11, male 82%, stage I:9%, II:15%, III:69%, IV:7%, adenocarcinoma: 78%, neoadjuvant therapy: 70%). Clinical stage I was associated with better QOL at diagnosis (131 ± 2 vs 118 ± 28, p < 0.02). FACT-E > 125 was associated with lower peri-operative mortality (9% vs 1%, 0R = 6.1, P = 0.01), and when divided into quintiles, correlated directly with OS (Figure 1a), more over it was able to prognostically differentiate patients with locally-advanced disease (stage II + III) (Figure 1b) better than the clinical staging (Figure 1c). Conclusion: QOL at diagnosis predicts peri-operative mortality and long-term survival. It can help to prognostically differentiate between patients with locally advanced disease. Attempts to improve QOL prior to surgery, such as with pre-habilitation, remain an attractive area of investigation.